An assessment of over-indebtedness among microfinance institutions’ borrowers: The Tanzanian perspective - Pendo Shukrani Kasoga; Amani Gration Tegambwage (Cogent Business & Management, 2021)
The introduction of microfinance institutions is viewed as the best alternative source of financial services for low-income earners as a means to raise their income and reduce poverty. However, empirical research has indicated that the majority of microfinance institutions’ borrowers are over-indebted. Over-indebtedness has negative consequences for debtors, creditors, and for the economy as a whole. Since over-indebtedness is a context-specific phenomenon, it lacks universally accepted indicators. This study aims to validate indicators of over-indebtedness and examine the situation of over-indebtedness among micro-borrowers in the context of Tanzania. A survey of 535 micro-borrowers was conducted using a semi-structured questionnaire. Descriptive, thematic, and logistic regression techniques were employed for data analysis. Findings show that debt-to-income ratio, multiple borrowing, and delinquency have a positive and significant effect on over-indebtedness. Further, findings indicate that over-indebted micro-borrowers in Tanzania spend 75% or more of monthly income on servicing debts; are in the state of delinquency; are unable to meet basic needs due to loan repayment expenditure, have three or more credit commitments, and are in delinquency. To reduce over-indebtedness and hence poverty among micro-borrowers, microfinance institutions are advised to monitor debt levels among micro-borrowers, and reschedule loan repayment plans to already over-indebted micro-borrowers.